A community-based prospective cohort study of dengue viral infection in Malaysia: the study protocol. Issue 1 (December 2016) - Jahan, Nowrozy; Ahmad, Mohtar; Dhanoa, Amreeta; Meng, Cheong; Ming, Lau; Reidpath, Daniel; Allotey, Pascale; Zaini, Anuar; Phipps, Maude; Fatt, Quek; Rabu, Aman; Sirajudeen, Rowther; et al.
Abstract Background Globally, dengue infections constitute a significant public health burden. In recent decades, Malaysia has become a dengue hyper-endemic country with the co-circulation of the four dengue virus serotypes. The cyclical dominance of sub-types contributes to a pattern of major outbreaks. The consequences can be observed in the rising incidence of reported dengue cases and dengue related deaths. Understanding the complex interaction of the dengue virus, its human hosts and the mosquito vectors at the community level may help develop strategies for addressing the problem. Methods A prospective cohort study will be conducted in Segamat district of Johor State in Peninsular Malaysia. Researchers received approval from the Malaysian Medical Research Ethics Committee and Monash University Human Research Ethics Committee. The study will be conducted at a Malaysian based health and demographic surveillance site over a 1 year period in three different settings (urban, semi-urban and rural). The study will recruit healthy adults (male and female) aged 18 years and over, from three ethnic groups (Malay, Chinese and Indian). The sample size calculated using the Fleiss method with continuity correction is 333. Sero-surveillance of participants will be undertaken to identify asymptomatic, otherwise healthy cases; cases with dengue fever who are managed as out-patients; and cases with dengue fever admitted to a hospital. A genetic analysis of the participants will be undertaken to determine whether there is a relationship between genetic predisposition and disease severity. A detailed medical history, past history of dengue infection, vaccination history against other flaviviruses such as Japanese encephalitis and Yellow fever, and the family history of dengue infection will also be collected. In addition, a mosquito surveillance will be carried out simultaneously in recruitment areas to determine the molecular taxonomy of circulating vectors. Discussion The research findings will estimate the burden of asymptomatic and symptomatic dengue at the community level. It will also examine the relationship between virus serotypes and host genotypes, and the association of the clinical manifestation of the early phase with the entire course of illness.